Unilateral Mistake: The Baseball Card Case - Andrew Kull (Washington University Law Quarterly, 1992)
Part I of this Article revisits the traditional account of unilateral mistake, arguing that a "subjective" theory focused on requirements of contract formation still provides the most convincing explanation of the case law and the best rule of decision. Part II suggests that the original limits to relief for unilateral mistake came to be expanded as an unintended consequence of the Holmes/Williston "objective theory" of contract, though the present-day consequences of this development are very far from what either scholar would have approved. Part III examines the alternatives to the traditional conception of unilateral mistake currently advanced by influential schools of modern contract theory.
Keywords: Rescission (Law); Mistake (Law); Irmen v. Wrzesinski